Size of Spodoptera exigua (Lepidoptera: Noctuidae) larvae Reared on Various Host Plants - Azidah, A.A.; Sofian-Azirun, Mohd (Faculty of Science, University of Malaya, 2007)
The study of the larval size of Spodoptera exigua based on their head capsule was performed on larvae reared on leaves of cabbage, shallot, long beans and lady's fingers. It was found that there was no significant difference in the larval head capsule size of the 1st instar among the studied host plants. However, for the subsequent larval instar stages (i.e. from the 2nd to 6th instars), there were significant difference among treatments. Comparatively, this study has found that larvae reared on long beans have a bigger head capsule size compared to those reared on the other host plants. Larvae reared on shallot have the smallest head capsule size.